A green approach for the treatment of oily steelworks wastewater using natural coagulant of Moringa oleifera seed - Edward Lester-Card (Bioresource Technology Reports, 2023)
A new approach to treat oily steelworks wastewater using a natural coagulant is reported. Moringa oleifera crude extract (MOCE) was used, and its efficiency was compared to traditional alum and synthetic polymer (Nalco 9908) by optimising pH, dose and settling time. Jar tests showed that MOCE caused rapid coagulation-flocculation kinetics and higher oil removal than alum and the polymer (95 %-MOCE, 71 %-alum and 48 %-polymer). Additionally, MOCE exhibited a wider effective pH range (pH 3–11) and did not affect the initial pH of the wastewater. However, MOCE produced higher sludge volume (35 mL/L) as compared to alum (25 mL/L), and the synthetic polymer only produced a sticky sludge stuck to the walls of the vessel. Tests on steelworks wastewater combining MOCE and the polymer produced a synergistic effect exhibiting reduced settling time and increased oil removal. Overall, this study shows that MO extracts have high potential in sustainable treatment of oily wastewaters.